PRINCIPLE SUBJECTIVITY IN LIGHT OF THE ACTIVITIES-ECONOMIC APPROACH - Савицька, Н. Л. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2012)
The article contains a methodological principle of subjectivity of economic activity, the corresponding theory of the economy. Highlighted the subject-object, subject-subject structure of economic activity on the basis of goal-setting and distinguish performance goals, stressed axiological nature of economic activity particularly in terms of becoming a knowledge economy.